Communicable Diseases Intelligence volume 7 issue 4 - 23 February 1983 - whole issue - No author listed, (Communicable Diseases Intelligence, 1983)
Whole-issue pdf, comprising: Virus Reporting Scheme Article Primary Amoebic Meningoencephalitis (PAM) [lengthy article] (Based on "Primary Amoebic Meningoencephalitis - an historical and epidemiological perspective with particular reference to South Australia" contributed by M.M. Dorsch, South Australian Health Commission) [see also CDI 83/9, page 23-24] Australia - Communicable Diseases Intelligence Reporting Period 03/02/1983 - 16/02/1983